Influence of Depleted Complement Activity on the Development of Zymosan-Induced Arthritis - Lyudmila Belenska-Todorova; Nina Ivanovska (Highlights on Medicine and Medical Research Vol. 4, 2021)
Zymosan-induced arthritis is an experimental model of rheumatoid arthritis used for analyzing cells and molecules that mediate the pathogenesis of inflammatory joint diseases. Although the alternative pathway of complement activity is involved in the pathogenesis of arthritis, many issues are not well elucidated. The aim of the present study was to evaluate the effect of complement depletion on cartilage integrity, Dectin-1 expression and apoptosis of blood monocytes and lymphocytes. The decomplementation was performed using cobra venom factor (CVF), a peptide fragment analogous to C3 component, which is capable of activating the alternative complement pathway. We established that CVF treatment reduced proteoglycan loss and differentially affected Dectin-1 expression on monocyte and lymphocyte populations along with decreased number of dendritic cells (DCs) in the synovial fluid. Success of complement inhibition in the experimental models encourages novel therapeutic approaches to the treatment of human rheumatoid arthritis.